2021
DOI: 10.3390/jfb12030051
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Year Comparative Evaluation of Clinical Performance of a Nanohybrid Composite Resin to a Flowable Composite Resin

Abstract: Objective: This prospective in vivo study aimed to compare the clinical behavior of a flowable composite resin (Genial Universal Flo, GC) and a nanohybrid universal composite resin (Tetric Evo Ceram, Ivoclar Vivadent) used in Class I and II direct esthetic restorations in posterior teeth. Methods: A total of 108 Class I and II direct restorations were performed in patients aged between 20 and 60 years. The originality of this study lies in the fact that both materials were placed in pairs, in the same clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Colour stability is a general problem for posterior teeth, but more significant for anterior teeth, which limits the use of composites [ 9 , 10 ]. The evaluation, adoption and implementation of new technologies are important in the identification of composite materials with improved physico-chemical and mechanical characteristics [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Colour stability is a general problem for posterior teeth, but more significant for anterior teeth, which limits the use of composites [ 9 , 10 ]. The evaluation, adoption and implementation of new technologies are important in the identification of composite materials with improved physico-chemical and mechanical characteristics [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A randomized controlled trial by Bhadra et al [28] in the year 2018 evaluated and compared the clinical performance of a nanohybrid composite with ACTIVA TM BioACTIVE restorative material in Class II cavities of permanent molars. e trial concluded that both materials showed equal and acceptable clinical performance at the end of 1 year [28].…”
Section: Discussionmentioning
confidence: 99%
“…It can produce mineralized tissue, preserve pulp vitality, and odontoblast layer integrity, and enhance mechanical properties. It is therefore recommended as a pulp capping agent [ 3 , 4 ]. Giomers combined the characteristics of composite resin with glass ionomer cement.…”
Section: Introductionmentioning
confidence: 99%